Status Quo and Prospect on Mobile Database Security - Tao Zhang; Shi Xing-jun (Institute of Advanced Engineering and Science, 2013)
Mobile database is a specialized class of distributed systems. There are some security challenges because of the dispersed nature of the mobile database application and hardware deviceconstraints. Therefore, the security issue of mobile database is analyzed in this paper. We will research the security in terms of mobile device, operating system on mobile device, mobile network and mobile database. Moreover, various security vulnerabilities on mobile database is recognized. Some appropriate technique is used to deal with side affect for mobile database security. For the sake of more security, Comprehensive solution that is applied to distributed database is proposed. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3228